Impact of Financial Indicators on Nepalese Commercial Bank Stock Prices - Pramod Dahal; Rajesh Gurung; Shiva Raj Ghimire (Interdisciplinary Journal of Management and Social Sciences, 2025)
This study examines the impact of key financial factors price-to-earnings ratio, book value per share, dividend rate, earnings yield, and market-to-book value ratio on the market prices of Nepalese commercial banks. Using descriptive statistics, correlation analysis, and multiple regression models, data from 209 annual observations spanning the fiscal years 2013/14 to 2023/24, provided by all Nepalese commercial banks listed on the Nepal Stock Exchange, were analyzed. The findings reveal a significant positive relationship between market price and both the price-to-earnings ratio and book value per share, indicating these variables play a critical role in determining stock prices. While the market-to-book value ratio, earnings yield, and dividend rate also demonstrated positive correlations, their impacts were less pronounced. These results emphasize the importance of profitability and valuation metrics in guiding investors' decision-making processes in the Nepalese stock market.